Pharmacokinetics of Angiotensin II Receptor Blockers in the Dog Following a Single Oral Administration - Baek, I.-H.; Lee, B.-Y.; Lee, E.-S.; Kwon, K.-I. (Drug Research, 2013)
Angiotensin II receptor blockers (ARBs) are effective and well-tolerated orally active anti-hypertensive agents. The purpose of this study was to investigate the pharmacokinetic properties of typical ARBs in the dog. 60 beagles were administered a single oral dose of Micardis® 80 mg (telmisartan), Cozaar® 50 mg (losartan), or Diovan® 80- and 160-mg (valsartan). The plasma concentrations of these ARBs were measured using liquid chromatography/tandem mass spectrometry and their pharmacokinetic properties were analyzed using both non-compartmental and compartmental approaches. The half-life and volume of distribution in dogs were in the order losartan>valsartan>telmisartan after oral administration. Systemic exposure was estimated by calculating the area under the plasma concentration-vs.-time curve from time zero to infinity (AUCinf), and resulted in the order telmisartan>valsartan>losartan. The values of Cmax and AUC increased in proportion to the dose of valsartan. In compartmental analysis, the pharmacokinetics of telmisartan and losartan pharmacokinetics fit a 2-compartment model, while valsartan fit a 1-compartment model. These results provide detailed pharmacokinetic information of ARBs in the dog, and may aid in future development of improved formulations or fixed-dose combinations.
Keywords: telmisartan; losartan; valsartan; pharmacokinetics; dog